OP0313 The Use and Impact of Social Media in Modern Rheumatology Practice Based on a Survey by the Emerging Eular Network (Emeunet). (9th June 2015) - Nikiphorou, E.; Studenic, P.; Jani, M.; Canavan, M.; Ospelt, C.; Ammitzbøll, C.G.
Abstract : Background: The use of social media (SM) platforms and networks is fast expanding yet their impact especially within the professional world is often under-appreciated and has not been systematically evaluated. Objectives: To perform an online survey on the use, perceptions and impact of SM within the rheumatology professional world and beyond. Methods: A questionnaire prepared by rheumatologists from different countries within the EMEUNET group was designed to assess perceptions and the impact of SM among users and non-users. EMEUNET is a Europe-wide network of more than 1000 young rheumatologists addressing educational needs and promoting research interests. The survey covered a range of questions from basic demographic information to perceptions on the use and impact of SM in a professional or other. The survey was advertised via three main routes: Twitter, Facebook and by direct email to EMEUNET members. Results: 233 anonymized responses were collected from 47 countries. The majority completed the survey via email (90%), the rest via Tw (6%) and FB (4%). 72% of responders were within the age group of 30-39 years. 66% were female; 51% were in a combined clinical/academic job setting. 83% were active users of at least one SM platform with a mean weekly use of 7 hrs, and 71% of those used SM in a work-related manner. The majority used SM for communicating with friends/colleagues (79%), news updates (76%), entertainment (69%), rheumatology clinical (50%) and research (48%) updates. Table 1 shows SM sites and the frequency of use. FB was the dominant SM platform with 91% using it although only 68% professionally, whereas LinkedIn was the dominant platform for professional-related communication. The latter included using SM as a source of information (81%); expanding professional networks (76%); new resources (59%); learning new skills (47%) and establishing a professional online presence (46%). Work-related SM users had a significantly increased use of SM (8 hrs weekly) of which 5 hours were work-related. The main obstacles for not using SM in a work-related manner were "lack of knowledge on how to do so" (44%) followed by "not suitable for individual needs" (30%). 9% were concerned regarding negative impact on their reputation. 68% felt that SM is a safe way of communicating with other people although of those not using SM 37% expressed concerns regarding its safety, exposure of private life and being a time-consuming process. 30% of non-SM users justified not using SM due to lack of knowledge; 26% considered SM unsuitable for their needs and 41% expressed no interest in SM. Conclusions: The results highlight that use of SM within rheumatology professionals and basic scientists is considerable, for social but mostly professional reasons. SM provides a good source of information for educational purposes and potential for networking. he lack of knowledge on how to use SM in a work related manner highlights the need for providing resources necessary to enable more widespread use of SM. Despite concerns regarding the safety of SM and exposure of private life, the majority of respondents had a positive view towards SM. Acknowledgements: We thank Dr David O'Reilly for his contribution. Disclosure of Interest: None declared